2021
DOI: 10.18632/aging.203238
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitor Trichostatin A suppresses adipogenesis in 3T3-L1 preadipocytes

Abstract: Background and purpose: Obesity is becoming a major global health issue and is mainly induced by the accumulation of adipose tissues mediated by adipogenesis, which is reported to be regulated by peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT enhancer-binding protein α (C/EBPα). Trichostatin A (TSA) is a novel histone deacetylase inhibitor (HDACI) that was recently reported to exert multiple pharmacological functions. The present study will investigate the inhibitory effect of TSA on adipogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Histone deacetylases catalyze DNA deacetylation and play a crucial role in the modulation of atherosclerosis [ 31 ]. TSD is an analog of trichostatin A (TSA), which is a pan-HDAC inhibitor [ 32 , 33 , 34 ]. Studies have found that inhibition of HDAC activity induced KLF2 expression, which then contributed to reducing inflammation of endothelial cells [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylases catalyze DNA deacetylation and play a crucial role in the modulation of atherosclerosis [ 31 ]. TSD is an analog of trichostatin A (TSA), which is a pan-HDAC inhibitor [ 32 , 33 , 34 ]. Studies have found that inhibition of HDAC activity induced KLF2 expression, which then contributed to reducing inflammation of endothelial cells [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…TSD is a structural analog of TSA. TSA is a known pan-inhibitor of HDACs that thereby regulating the expression of related genes [ 32 , 33 , 34 ]. It was reported that HDAC4, 5, and 7 inhibited KLF2 expression, which in turn had an important role in anti-inflammation, sepsis, and angiogenesis [ 16 , 35 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…iWAT was divided into smaller pieces and digested in phosphate-buffered saline (PBS, Hyclone, Logan, UT, USA) with 0.5 mg/mL collagenase I (Worthington Biochemical Corporation, Lakewood, NJ, USA) at 37 °C for 1.5 h. After digestion, samples were filtered sequentially through nylon filters with a pore size of 600 and 50 µm, and centrifuged at 800 rpm for 5 min. According to the typical induction cocktail method [ 20 , 21 , 22 ], the obtained SVF cell pellet was then resuspended in the complete medium, which containing 89% Dulbecco’s modified Eagle’s medium (DMEM/F12, Gibco, Grand Island, NY, USA), 10% fetal bovine serum (FBS, Gibco, Grand Island, NY, USA) and 1% penicillin and streptomycin (PS, Hyclone, Logan, UT, USA). Resuspended SVF cells were incubated in 6-well plates at a concentration of 8 × 10 4 cells/well maintained at 37 °C in the presence of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…400 Trichostatin A (TSA) is a novel HDACi and reportedly inhibits adipogenesis in 3T3-L1 preadipocytes through the AMPK signalling pathway. 401 By inhibiting HDAC and increasing insulin sensitivity, sodium acetate alleviates hepatic lipotoxicity related to diabetes. 402 Puerarin may attenuate diabetic osteoporosis by preventing inflammation and apoptosis through HDAC1 and HDAC3 inhibition.…”
Section: Epigenetic Therapymentioning
confidence: 99%